Program Darling (Tadarus Keliling) Sebagai Strategi Peningkatan Kemampuan Public Speaking Santri - Yada, Kholifatin Maha; Mumtahana, Lusia (Universitas KH. Abdul Chalim Pacet Mojokerto, 2024)
The study on improving the public speaking skills of T.P.Q. Muhammadiyah Menongo Sukodadi Lamongan students uses a qualitative research method with a descriptive approach. This research aims to describe the